Pembelajaran Daring Matematika Melalui Media Quizizz Berhadiah Dalam Meningkatkan Minat Belajar Pelajar SMPN 58 Surabaya - d, dian arleni (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2021)
This research was conducted with the aim of knowing the impact of online learning methods, as well as the impact of using Quizizz as a learning media with prizes on student interest in learning at SMP Negeri 58 Surabaya. Data collection methods used by researchers in this study are observation, interviews, and documentation. The data analysis technique used is descriptive exploratory method which aims to describe and conclude the impact of using online learning methods for Mathematics, and the impact of using Quizizz media with prizes on student interest in learning. The results of this study can be seen: (1) in the use of online learning methods for Mathematics, student understanding has increased 58.3% from the previous condition. (2) the use of Quizizz learning media with prizes has an impact on student learning patterns, such as: level of concentration, memory, comprehension, durability of learning time, and an increase in student understanding, which is seen from the increase in the percentage level of student learning outcomes by 83. 3%.